2022
DOI: 10.1186/s12889-021-12465-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with habitual sleep duration in US adults with hypertension: a cross-sectional study of the 2015–2018 National Health and Nutrition Examination Survey

Abstract: Background The relationship between inadequate sleep duration and hypertension risk has been established in the general population, but there is a gap in the literature on predictors of habitual sleep duration in adults with hypertension. This study examined factors associated with habitual sleep duration among adults with hypertension in the United States (US). Methods Data of 5660 adults with hypertension were obtained by combining the 2015–2018 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Echoing our ndings, Yujie Li's team identi ed short nocturnal sleep duration as an independent risk factor for the onset and persistence of depression among elderly Chinese individuals [28]. Furthermore, a longitudinal study revealed a higher prevalence of depressive symptoms among those sleeping less than 5 hours compared to those with optimal sleep durations (7-8 hours) [29]. Strikingly, another study found that individuals sleeping less than 6 hours per night had a four-fold increased risk of depression compared to those sleeping 7-8 hours [30].…”
Section: Discussionmentioning
confidence: 97%
“…Echoing our ndings, Yujie Li's team identi ed short nocturnal sleep duration as an independent risk factor for the onset and persistence of depression among elderly Chinese individuals [28]. Furthermore, a longitudinal study revealed a higher prevalence of depressive symptoms among those sleeping less than 5 hours compared to those with optimal sleep durations (7-8 hours) [29]. Strikingly, another study found that individuals sleeping less than 6 hours per night had a four-fold increased risk of depression compared to those sleeping 7-8 hours [30].…”
Section: Discussionmentioning
confidence: 97%
“…9,10,11,12 Multiple dimensions of sleep health, including insu cient sleep duration, irregular sleep schedules, and poor sleep quality, can increase cardiometabolic risk predisposing to CVD. 13 For instance, poor sleep has been linked to higher risk for hypertension, 14,15 obesity, 16 and type 2 diabetes 17 via theorized mechanisms including in ammation 18,19 , glycemic dysregulation, 20 increased sympathetic tone via increases in nocturnal catecholamines. 21 Thus, this connection suggests a possible mechanism explaining the adverse impact of EHEs on CVD, with sleep as a mediating factor, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%